The Influence of Customer Motivation, Personal Selling and Product Quality on Purchasing Decisions of King Crab brand rice at PT Bendy Jaya Mandiri Medan - Situmeang, Rosinta Romauli; Winata, Steven; Cen, Felix; ., Steven (2020)
The purpose of this study was to examine and analyze the influence of Customer Motivation, Personal Selling and Product Quality on Purchasing Decisions of king crab brand rice at PT Bendy Jaya Mandiri Medan. Decrease in the Purchase Decision of Crab King brand rice at PT Bendy Jaya Mandiri Medan is caused by Customer Motivation, Personal Selling and Product Quality. The theory used is related to Customer Motivation, Personal Selling and Product Quality after the Purchase Decision. The population in this study amounted to 194 customers and a sample of 134 customers. The sampling technique used was random sampling. The data analysis used was validity and reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing. The conclusion in this study is that partially and simultaneously Customer Motivation, Personal Selling and Product Quality have a positive and significant effect on purchasing decisions of king crab brand rice at PT Bendy Jaya Mandiri Medan.